SIMULASI PEMILAH BENDA BERDASARKAN WARNA (HITAM-PUTIH) MENGGUNAKAN SENSOR WARNA BERBASIS MIKROKONTROLER AT89S51 - Sandi apriandi; Mohamad Amin HD; Sri Dianing Asri (Jurnal Algoritma, Logika dan Komputasi, 2019)
At present the company is always trying to replace the work done by humans, replaced by machines in order to improve the efficiency and quality of production. In other words, many companies automate their production. For example, production processes that were initially carried out manually as in the process of sorting their products. In the industry this process is done manually with human effort and requires a large amount of labor and makes the production process longer. To overcome this problem, companies that want more effective and efficient production processes to change production patterns by applying automation in their production systems. This is realized by the construction of a packing system for goods, where the system usually consists of goods distribution in the form of a mechanical conveyor system and packaging of goods. As in the case of items based on the color sorting system, you will need a tool that can automatically sort this product. This system consists of object sensors, color sensors, conveyor belts, and means of dividing goods. Mechanical systems are built using acrylic, plastic and PVC. The control system in this simulation uses the AT89s51 IC microcontroller.Keyword : Augmented Reality, Satya Negara Indonesia University, Virtual Reality, 3D